Predictors for Glucose Change in Hypertensive Participants Following Short‐term Treatment with Atenolol or Hydrochlorothiazide. Issue 11 (9th September 2014) - Moore, Mariellen J.; Gong, Yan; Hou, Wei; Hall, Karen; Schmidt, Siegfried O. F.; Curry, Robert Whitney; Beitelshees, Amber L.; Chapman, Arlene; Turner, Stephen T.; Schwartz, Gary L.; Bailey, Kent; Boerwinkle, Eric; et al.
<x xml:space="preserve">Abstract</x> Study Objective To develop and validate a predictive model for glucose change and risk for new‐onset impaired fasting glucose in hypertensive participants following treatment with atenolol or hydrochlorothiazide (HCTZ). Design Randomized multicenter clinical trial. Patients A total of 735 white or African‐American men and women with uncomplicated hypertension. Measurements and Main Results Pharmacogenomic Evaluation of Antihypertensive Responses (PEAR) is a randomized clinical trial to assess the genetic and nongenetic predictors of blood pressure response and adverse metabolic effects following treatment with atenolol or HCTZ. To develop and validate predictive models for glucose change, PEAR participants were randomly divided into a derivation cohort of 367 and a validation cohort of 368. Linear and logistic regression modeling were used to build models of drug‐associated glucose change and impaired fasting glucose (IFG), respectively, in the derivation cohorts. These models were then evaluated in the validation cohorts. For glucose change after atenolol or HCTZ treatment, baseline glucose was a significant (p<0.0001) predictor, explaining 13% of the variability in glucose change after atenolol and 12% of the variability in glucose change after HCTZ. Baseline glucose was also the strongest and most consistent predictor (p<0.0001) for development of IFG after atenolol or HCTZ monotherapy. The area under the receiver operating curve was 0.77 for IFG after atenolol and 0.71 after HCTZ treatment, respectively. Conclusion Baseline glucose is the primary predictor of atenolol or HCTZ‐associated glucose increase and development of IFG after treatment with either drug.